2019
DOI: 10.18203/2320-6012.ijrms20192910
|View full text |Cite
|
Sign up to set email alerts
|

Current clinical trends in the management of gram positive infections in Indian critical care settings: a survey

Abstract: Background: In India, gram-positive infections (GPIs) particularly, methicillin-resistant Staphylococcus aureus (MRSA) prevalence is reported to increase exponentially. The overall mortality rate among patients with multi drug resistant GPIs in ICU setting are as high as 16%, despite the availability of various therapeutic options. Aim of the study is to determine the burden of GPIs in critical care settings and to understand the practising behaviour among the specialists in the management of MRSA infections.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Ultimately, only 34 of 40 studies were included in the MRSA meta-analysis, 8,9,15 -46 as the remaining 6 studies did not include data relevant to MRSA (4 efficacy studies, 1 study that described heteroresistance to vancomycin among methicillin-resistant S. aureus isolates, and 1 survey wherein no exact data on prevalence were presented). 47 -52 Table 1 represents the characteristics of the studies included in the analysis. The studies included in the systematic literature review did not include randomized controlled trials so risk-bias analysis was not performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, only 34 of 40 studies were included in the MRSA meta-analysis, 8,9,15 -46 as the remaining 6 studies did not include data relevant to MRSA (4 efficacy studies, 1 study that described heteroresistance to vancomycin among methicillin-resistant S. aureus isolates, and 1 survey wherein no exact data on prevalence were presented). 47 -52 Table 1 represents the characteristics of the studies included in the analysis. The studies included in the systematic literature review did not include randomized controlled trials so risk-bias analysis was not performed.…”
Section: Resultsmentioning
confidence: 99%
“…50 The survey conducted by Rampal et al, indicated an increasing trend in the prevalence and associated mortality in Grampositive bacterial infections in critical care settings in India. 52 The limitations of the existing anti-MRSA agents necessitate the development of a newer agent with a broad spectrum antibacterial activity along with an improved safety profile.…”
Section: Secondary Outcomementioning
confidence: 99%
“…A survey of the trends in the management of GPIs in Indian critical care settings highlighted an increasing trend in prevalence and associated mortality with GPIs [12]. To address the challenge of growing multidrugresistant pathogens and limitations associated with existing anti-MRSA agents, there is a need for a new suitable empirical agent with an improved safety profile, especially in the ICU [9]. The Infectious Disease Society of America guidelines emphasizes adequately controlling the source of infection, such as draining abscesses and debridement of nonviable tissues irrespective of the AMAs used [13].…”
Section: Discussionmentioning
confidence: 99%
“…In India, high rates of MRSA have been reported among the S. aureus pool in clinical isolates from various studies, with rates as high as 54.8% (range, 32% to 80%) [8]. Despite the availability of various antimicrobial agents (AMAs), the intensive care unit (ICU) mortality in patients with multidrug-resistant Gram-positive infections (GPIs) is up to 16% [9].…”
Section: Introductionmentioning
confidence: 99%